Pre‐Sunrise Equatorial Plasma Bubble Over Indonesia During the 11 May 2024 Super Geomagnetic Storm - Suraina; A. Rakhman; P. Abadi; L. O. M. M. Kilowasid; A. Y. Putra; S. Perwitasari; T. M. Irnaka (Earth and Space Science)
Abstract Equatorial Plasma Bubbles (EPBs) generally form around sunset in equatorial to low‐latitude regions. However, based on observations of the rate total electron content (TEC) change index (ROTI) map over Indonesia and the ionosonde data from the Southeast Asian equatorial station during the super geomagnetic storm on 11 May 2024, we report that EPBs did not form during the post‐sunset period. Instead, EPBs were observed to form pre‐sunrise in the Indonesian region, an event that occurs rarely. These EPB structures developed and strengthened as they evolved and extended poleward. We suspect that the EPBs formed during the pre‐sunrise period were caused by the eastward disturbance dynamo electric field (DDEF), which begins around midnight and continues until sunrise. As a result, plasma bubbles started forming near sunrise and survived until the morning. Observations from three ground‐based GPS stations in Southeast Asia on May 11th, showed a significant decrease in TEC caused by EPBs pre‐sunrise. However, no GNSS scintillation was detected during this period. In contrast, strong scintillation was observed at mid‐latitudes. Before the formation of the EPB pre‐sunrise, the peak height of the ionospheric F layer experienced a significant increase, likely caused by the DDEF during the recovery phase. The rise in the F layer height could support the growth rate of Rayleigh‐Taylor instability. Therefore, DDEF becomes a major contributor to the formation of EPBs pre‐sunrise.